Development of Visible Light-Responsive Sensitized Photocatalysts - Donghua Pei; Jingfei Luan (International Journal of Photoenergy)
The paper presents a review of studies about the visible-light-promoted photodegradation of the contaminants and energy conversion with sensitized photocatalysts. Herein we studied mechanism, physical properties, and synergism effect of the sensitized photocatalysts as well as the method for enhancing the photosensitized effect. According to the reported studies in the literature, inorganic sensitizers, organic dyes, and coordination metal complexes were very effective sensitizers that were studied mostly, of which organic dyes photosensitization is the most widely studied modified method. Photosensitization is an important way to extend the excitation wavelength to the visible range, and therefore sensitized photocatalysts play an important role in the development of visible light-responsive photocatalysts for future industrialized applications. This paper mainly describes the types, modification, photocatalytic performance, application, and the developments of photosensitization for environmental application.